Last postglacial environmental evolution of the Laptev Sea shelf as reflected in molluscan, ostracodal and foraminiferal faunas - Taldenkova, Ekaterina; Bauch, Henning A.; Stepanova, Anna; Dem'yankov, S.; Ovsepyan, A. (Global and Planetary Change, 2005)
Temporal and spatial variations in the species composition of modern and Holocene assemblages of molluscs, ostracods, and foraminifers from the Laptev Sea shelf (Arctic Siberia) have been investigated to reconstruct palaeoenvironmental changes during the last postglacial times and associated sea-level rise. Analysis of coretop sediment samples allowed to distinguish four modern assemblages. The specific habitat preferences of these species groups, such as water depth and salinity, were then used to interpret past environmental changes on the basis of two radiocarbon-dated sediment cores from the eastern middle shelf region, i.e., obtained from the Yana (51 m water depth) and Lena (45 m water depth) palaeovalleys. Despite the water depth difference of the two core sites, all downcore data document uniform fossil evidence for a gradual transformation of the Laptev Sea shelf from a terrestrial to a marine environment due to the southward transgressing sea. Three major phases have been recognized. These reflect: (1) a nearshore brackish-water environment of the initial stage of inundation (11.3–11.1 in the Yana and 11.2–10.8 cal. ka in the Lena palaeovalley); (2) a shallow inner-shelf, fluvially affected environment (11.1–10.3 and 10.8–8.2 cal. ka); (3) a modern-like marine environment which eventually became established since 10.8 and 8.2 cal. ka, depending on the specific water depth of each core site.